Employment and Taxes - Stephen Nickell (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper considers the impact of taxation policy on market work. On the basis of the evidence, we find that a 10 percentage point rise in the tax wedge will reduce overall labour input provided via the market by around 2 per cent of the population of working age. The tax wedge is the sum of the payroll, income and consumption tax rates. This only explains a minority of the market work differentials across countries. Much of the remainder is probably down to the differences in the social security systems supporting the unemployed, the sick and disabled and the early retired.
Keywords: 330; employment; taxation; labour supply